2007
DOI: 10.1016/j.physd.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficient data assimilation for spatiotemporal chaos: A local ensemble transform Kalman filter

Abstract: Data assimilation is an iterative approach to the problem of estimating the state of a dynamical system using both current and past observations of the system together with a model for the system's time evolution. Rather than solving the problem from scratch each time new observations become available, one uses the model to "forecast" the current state, using a prior state estimate (which incorporates information from past data) as the initial condition, then uses current data to correct the prior forecast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
1,823
0
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,368 publications
(1,843 citation statements)
references
References 48 publications
9
1,823
0
11
Order By: Relevance
“…Observation localization (OL; Hunt et al 2007) suppresses spurious correlations associated with distant locations and increases the rank of the analysis covariance by partitioning the state vector into subsets, the so-called local domains. Typically, a local domain contains all state variables at each grid point or in each vertical column (e.g., Houtekamer and Mitchell 1998;Losa et al 2012).…”
Section: Localization and Inflationmentioning
confidence: 99%
See 1 more Smart Citation
“…Observation localization (OL; Hunt et al 2007) suppresses spurious correlations associated with distant locations and increases the rank of the analysis covariance by partitioning the state vector into subsets, the so-called local domains. Typically, a local domain contains all state variables at each grid point or in each vertical column (e.g., Houtekamer and Mitchell 1998;Losa et al 2012).…”
Section: Localization and Inflationmentioning
confidence: 99%
“…Over the past two decades, the EnKF has evolved to a robust scheme that is applicable to largescale systems with small ensemble sizes, such as in numerical weather prediction (e.g., Reich et al 2011;Miyoshi and Kunii 2012) or oceanography (e.g., Nerger et al 2007;Losa et al 2012). Deterministic variants such as the (local) ensemble transform Kalman filter [(L)ETKF, Bishop et al 2001;Hunt et al 2007] avoid sampling noise in the analysis step by applying a matrix square root transform. However, the implicit Gaussian assumption leads to a linear update mechanism and renders the analysis suboptimal in nonlinear systems (Lei and Bickel 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Miyoshi et al (2016aMiyoshi et al ( , 2016b reported an innovation of the "Big Data Assimilation" (BDA) technology, implementing a 30-second-update, 100-m-mesh local ensemble transform Kalman filter (LETKF; Hunt et al 2007) to assimilate data from a Phased Array Weather Radar (PAWR) at Osaka University (Ushio et al 2014) into regional NWP models known as the Japan Meteorological Agency non-hydrostatic model (JMA-NHM, Saito et al 2006Saito et al , 2007 and the Scalable Computing for Advanced Library and Environment-Regional Model (SCALE-RM, Nishizawa et al 2015). The PAWR captures the rapid development of convective activities every 30 seconds at approximately 100-m resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, much attention has been paid to skillful NWP for severe weather (e.g., Kain et al 2006, Hohenegger and Schär 2007a, b;Kawabata et al 2007;Roberts and Lean 2008). Recently, the ensemble Kalman filter (EnKF;Evensen 1994Evensen , 2003 has become a major method in data assimilation (DA), and has contributed to investigate convection-permitting regional NWP (e.g., Zhang et al 2007;Stensrud et al 2009Stensrud et al , 2013Clark et al 2010;Schwartz et al 2010; Baldauf et al 2011;Melhauser and Zhang 2012; Yussolf et al 2013, Kunii 2014a, Weng and Zhang 2016.Recently, Miyoshi et al (2016aMiyoshi et al ( , 2016b reported an innovation of the "Big Data Assimilation" (BDA) technology, implementing a 30-second-update, 100-m-mesh local ensemble transform Kalman filter (LETKF;Hunt et al 2007) to assimilate data from a Phased Array Weather Radar (PAWR) at Osaka University (Ushio et al 2014) into regional NWP models known as the Japan Meteorological Agency non-hydrostatic model (JMA-NHM, Saito et al 2006Saito et al , 2007 and the Scalable Computing for Advanced Library and Environment-Regional Model (SCALE-RM, Nishizawa et al 2015). The PAWR captures the rapid development of convective activities every 30 seconds at approximately 100-m resolution.…”
mentioning
confidence: 99%
“…The KENDA system implements for the COSMO model the LETKF scheme described by Hunt et al (2007). In this implementation, the method is fully four dimensional, that is all observations collected during the assimilation 5 window contribute to determine the analysis and the related model equivalents are computed using the prognostic variables at the proper observation time.…”
Section: The Kenda Systemmentioning
confidence: 99%